Sensitivity of Self-reported Opium Use in Cancer Patients: Implications for conducting epidemiological studies - Vahideh Mohseni; Maryam Hadji; Mina Khaki; Omid Nabavian; Kazem Zendehdel; Hamideh Rashidian (Basic & Clinical Cancer Research)
Background: Underreporting bias related to opium use is a significant methodological issue that can threaten the results of epidemiologic studies, particularly when opium use is the exposure of interest. In our current study, we aimed to measure the sensitivity of opium use. among cancer patients and identify the contributing factors